Patient reported experiences and treatment outcomes of orthodontic patients treated within secondary care settings in the South West of England during the COVID-19 pandemic. (March 2022) - Jopson, Jenifer L; Ellis, Pamela E; Jerreat, Amelia S; Kneafsey, Louise C; Moore, Matthew B; Day, Christian; Scott, Julia K; Griffiths, Helen; Lee, Tara VN; Oliver, Graham R; Fowler, Peter V; Sherriff, Martyn; et al.
Objective: To assess the impact of the temporary cessation of orthodontic services on patients undergoing treatment during the COVID-19 pandemic. Design: Two-phase multicentre service evaluation. Setting: Secondary care orthodontic departments in the South West of England. Materials and Methods: Phase 1 – Patient-Reported Experience Measure questionnaire (PREM). The questionnaire was distributed to patients who had undergone orthodontic treatment during the COVID-19 pandemic once services had resumed. Phase 2 – assessment of treatment outcomes, specifically with the Peer Assessment Rating (PAR) Index. A total of 280 PAR scores were obtained from a cohort of patients treated before and during the pandemic. Results: A total of 711 PREM questionnaires were completed. Participants generally felt relaxed when visiting secondary care settings, orthodontic departments and whilst wearing orthodontic appliances during the pandemic. Nearly 40% of participants were concerned that the pandemic would impact on their treatment, particularly treatment length. Treatment outcomes revealed that patients treated before and during the pandemic experienced percentage PAR score reductions of 83.9% and 80.6%, respectively. Patients receiving treatment during the pandemic experienced longer treatment durations of 126 days. Conclusion: During the pandemic, low levels of anxiety were reported with respect to receiving orthodontic treatment in secondary care settings. Irrespective of the pandemic, a high standard of orthodontic treatment was provided. However, patient concerns regarding treatment length were justified.